(untitled) (Research, Society and Development, 2020)
The objective is to realize the climatic aptitude and its potentiality for the cassava culture in the State of Pernambuco through the identification and quantification of climatic elements, followed by the elaboration of the mapping of its climatic aptitude. Used from monthly rainfall indexes of series with 35 years or more of continuous records. The Thornthwaite and Mather water balance method was applied to calculate the intermunicipal balances, considering 125 mm as the average water storage capacity in the soil and the moisture index calculated. The data were specialized and charts of the referred climatic parameters. The humidity index and the climatic factors determined two classes C3 (Moderate due to excess water) and C2 (Plena with prolonged rainy season), determinants for fitness. climate change in the state.